Effects of sleep deprivation on typical neurotransmitters - Wang Xuanyi (E3S Web of Conferences, 2024)
Several evidence suggests that sleep deprivation (SD) leads to significant changes in the function of neurotransmitter receptors in different nerve cell types. So far, research in this area has focused on brain regions that promote wakefulness and sleep and the hippocampus, which is involved in learning and memory. When wakefulness is longer than the natural duration, there are some selective disruptions in the brain’s sensory processing and cognitive performance.The author of this article discusses sleep deprivation and brain self-clearance patterns, and then explores the relationship between three typical neurotransmitters and sleep deprivation, as well as the detection and change trends of neurotransmitters and their metabolites.It can then be used to assist in the early diagnosis of certain diseases.Of the three neurotransmitters, two can be defined as pleasure neurotransmitters and one is associated with the degenerative neurological disease AD(Alzheimer’s disease). The author also found that there are different response patterns between these neurotransmitters and SD.